Evaluation of the effectiveness of dose individualisation to achieve therapeutic vancomycin concentrations - Abulfathi, Ahmed Aliyu (Stellenbosch : Stellenbosch University, 2017)
Thesis (MMed)--Stellenbosch University, 2017.